Intervención fisioterapeuta en paciente de sexo masculino de 26 años con lesión del ligamento cruzado anterior de la rodilla en la Federación Deportiva de Los Ríos – Babahoyo. - Lombeida Guillen, Cesar David (2023)
The present case study refers to the physiotherapist intervention in a 26-year-old male patient with an injury to the anterior cruciate ligament of the knee in the Babahoyo sports federation. This injury occurred due to hyperextension of the knee when he was playing soccer. to consultation due to pain, edema of the affected limb, alteration in gait, and limited joint mobility. By performing the corresponding tests, the diagnosis is determined and the respective physiotherapy treatment proceeds, which was completed and carried out within the established time, having a successful result. Anomalies of the knee, both of inflammatory and traumatic origin, are the main reason why they go to consultation. The knee has several muscular structures, including the anterior cruciate ligament, whose function is to limit displacement movement and limit the rotation of the tibia. The incidence of this type of injury is high in people who play soccer, whether professionally or amateur, and many of them end up in surgery, or with a great limitation in mobility since they did not have a physiotherapy plan, either due to lack of knowledge, due to poor practice or early abandonment, so the main objective of the case study is to determine the physiotherapy intervention that, carried out correctly and in a timely manner, results in the expected result. The present case study refers to the physiotherapist intervention in a 26-year-old male patient with an injury to the anterior cruciate ligament of the knee in the Babahoyo sports federation. This injury occurred due to hyperextension of the knee when he was playing soccer. to consultation due to pain, edema of the affected limb, alteration in gait, and limited joint mobility. By performing the corresponding tests, the diagnosis of anterior cruciate ligament injury was determined and the respective physiotherapy treatment was carried out, which was completed and carried out within the established time, having a successful result.